Metal oxide nanostructures as gas sensing devices - Eranna, G. (Boca Raton, FL : CRC Press, 2012)
'With an emphasis on gas (vapor) detection techniques using metal oxide nanomaterials, this book presents the complete list of nanostructured metal oxides and their syntheses. From aluminum to zinc, it analyzes metal oxides and their response to different gaseous (vapor) species. It also analyzes gaseous species from acetic acid to toluene. Numerous tables highlight the synthesis, operating range, responding gases, and response time of various metal oxides. The author details their nanostructures and shapes and explores active devices that use these materials, including future devices and gas sensing arrays such as e-nose. (1) Presents important information on gas sensing devices with an emphasis on future devices (2) Lists the different nanostructured metal oxides useful for gas sensing applications (3) Describes ways of synthesizing these metal oxide nanostructures and identifying the suitable nanostructured material for specific gases and gas mixtures (4) Provides a matrix for nanostructured material versus different pollutant gases and volatile organic compounds (VOCs) suitable for e-nose applications'--
Includes bibliographical references (p. 291-308) and index.
Keywords: Gas detectors; Metallic oxides -- Microstructure; Metallic oxides -- Synthesis; Nanostructures